Sistem Zonasi Sekolah: Antara Persepsi Dan Minat Belajar Siswa - Gede Danu Setiawan; Ni Luh Yaniasti (Indonesian Journal of Learning Education and Counseling, 2021)
This research aimed to find out the students’ perception about the school zoning system and the students’ learning interests from the seventh grade junior high school in Buleleng regency, as well as the effect of it. This research used correlation-quantitative research. The subject of this research was the students of seventh grade junior high school in Buleleng regency. The object of this research was the students’ learning interests affected by the students’ perception about the school zoning enrolment system for the new students. The data were taken by spreading the questionnaires, doing the observation and interviewing. The respondent in this research were 318 students of seventh grade junior high school in Buleleng regency who chosen randomly from each school. There were two variables in this research, the students’ perception about the school zoning system (X) and the students’ learning interests (Y). This research was analysed by using one sample t-Test, linier test and simple linear regression test. The results showed that: (1) students' perception of school zoning system for junior high students in Buleleng regency have been carried out so well. Also, the facilities and the infrastructures already supported the policy properly. The results showed an average number on 38,317 and the t-Test showed 29,196. (2) The students' learning interests in junior high school Buleleng regency showed a quite good result. This statement was supported by the average number on 2.7758 and the T-test was 29,20. (3) There was a significant result between the students’ perception about the school zoning system and the student’s learning interest. This result was supported by doing an analysis of independent sample t-Test analysis with a t-count showed 1,848 > 1,655 with percentage 56%.